VOCATIONAL TRAINING OF CHILDREN WITH VISUAL IMPAIRMENT - Zulaikho Khusnuddinova; Jasmina Torayeva; Durdona Rakhimova (Web of Journals Publishing, 2023)
This article talks about the peculiarities of vocational training of children with visual impairments. The difficulties, problems and solutions faced in the process of vocational training of children with visual impairments are described.
Keywords: children with visual impairment, vocational, professional training, rehabilitation, tiflopedagog, psychologist.